Information Asymmetry: Mediator between Promotions and Usage of Traditional Medicine in Central Uganda - Sarah, Nabachwa; Nixon, Kamukama; Odhiambo Joseph, Owino; Kijjambu Fredrick, Nsambu (British Journal of Marketing Studies, 2019)
There has been an overwhelming usage for traditional medicine (TM) in the recent times despite several developments in modern medicine. The increased demand is attributable to a number of factors among which is the aggressive promotions from the Traditional Health Practitioners (THPs). The TM promotions are however, suspected to be incomplete, inconsistent and inadequate which could explain the increased TM usage but the empirical evidence is limited. The study therefore set out to empirically test the mediating effect of information asymmetry on the relationship between promotions and consumer usage behavior of TM. A sample size of 369 participants was determined using Crochran’s formula, and a structured questionnaire was administered using a face-to-face approach. SPSS Statistics 20 was used to run the preliminary analysis while SPSS AMOS 23 was used to test for mediation using bootstrapping. The results showed that information asymmetry is a significant partial mediator in the relationship between promotions and consumer usage behavior of TM users. In conclusion therefore, the study provides empirical evidence of the role of information asymmetries and their effect on TM usage. The findings should aid policymakers in their understanding of the influence of TM promotions and information asymmetry on the majority Ugandans, hence guide the formulation of laws and policies on TM promotions. The main study limitation was the cross-sectional approach used; hence a longitudinal approach should be explored to examine this mediation effect across time. There is also need to understand information asymmetry from the THPs’ perspectives.